Spatiotemporally Controlled Formation and Rotation of Magnetic Nanochains In Vivo for Precise Mechanotherapy of Tumors. (22nd November 2022) - Fu, Qinrui; Feng, Hongjuan; Liu, Luntao; Li, Ziqiao; Li, Jianjie; Hu, Jing; Hu, Chengzhi; Yan, Xiaohui; Yang, Huanghao; Song, Jibin
Abstract: Systemic cancer therapy is always accompanied with toxicity to normal tissue, which has prompted concerted efforts to develop precise treatment strategies. Herein, we firstly develop an approach that enables spatiotemporally controlled formation and rotation of magnetic nanochains in vivo, allowing for precise mechanotherapy of tumor. The nanochain comprised nanocomposites of pheophorbide‐A (PP) modified iron oxide nanoparticle (IONP) and lanthanide‐doped down‐conversion NP (DCNP). In a permanent magnetic field, the nanocomposites would be aligned to form nanochain. Next, MnO2 NPs were subsequently administered to accumulate in tumor as suppliers of Mn 2+, which coordinates with PP to immobilize the nanochain. In a rotating magnetic field, the nanochain would rapidly rotate, leading to apoptosis/necrosis of tumor cell. The nanochain showed high T 2 ‐MR and NIR‐II fluorescence imaging signals, which facilitated guided therapy. The strategy has great potential in practical applications. Abstract : A dual‐mode imaging‐guided cancer mechanotherapy was developed through in situ assembly and spinning of magnetic nanochains. This novel therapeutic modality could be suitable for precise yet effective cancer treatment in local regions.